1989
DOI: 10.1016/0014-5793(89)80662-3
|View full text |Cite
|
Sign up to set email alerts
|

The gate of mitochondrial porin channel is controlled by a number of negative and positive charges

Abstract: Negatively charged carboxyl groups of mitochondrial porin have been converted into positively charged ones by means of reaction with water-soluble carbodiimide in the presence of ethylenediamine. Properties of channels formed in a planar lipid bilayer by native and modified porins are compared. Amidation has only little influence on the porin channel-forming activity as well as on the open-state conductance of the channel. However, the modification results in a significant enhancement of the voltage dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…At such low pH values, acidic charges are being neutralized, which increases the net effective positive charge involved in gating. Indeed, the involvement of many positive as well as negative charges in VDAC gating has been suggested previously (14). When pH was reduced symmetrically at both sides of the membrane, the pK a values calculated for n (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…At such low pH values, acidic charges are being neutralized, which increases the net effective positive charge involved in gating. Indeed, the involvement of many positive as well as negative charges in VDAC gating has been suggested previously (14). When pH was reduced symmetrically at both sides of the membrane, the pK a values calculated for n (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Correspondingly, neutralization of acidic charges leads to the increase of voltage-induced channel closure (11,14,32). A representative experiment illustrated by To quantify voltage-gating parameters upon acidification, we used a previously described approach (1,17,25,33).…”
Section: Acidification Increases Voltage Sensitivity Of Vdac-asmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work is in progress at present to localize the FITC-modified lysines within the primary structure of the mitochondrial porin. groups [13] has presented evidence that as many as 22 positively charged groups could be involved in channel gating. This would mean that almost all basic amino acids present in the primary structure are involved in some 'delocalized' gating and that no cluster of gating charges exist within the channel-forming unit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, such active groups were found in the molecular structures of molecules of voltage-dependent, ryanodine-sensitive, and inositol trisphosphate calcium channels [16,17]. It was also demonstrated that changes in the level of ionization of these groups can effectively modulate the functioning of transport systems [18,19]. The existence of active SH and COOH groups was also shown in the composition of channel molecules of MPTPs.…”
Section: Introductionmentioning
confidence: 99%